ПРОБЛЕМИ ВИЗНАЧЕННЯ СУБ’ЄКТИВНОЇ СТОРОНИ «ПРОПАГАНДИ ВІЙНИ» - Пекар, Павло Васильович; Андріанова, Тетяна Юріївна (SUPREMANCE OF LAW, 2018)
The article is devoted to the issues of determining the subjective part of the crime envisaged art. 436 of the Criminal Code of Ukraine “Propaganda of war”. It examines its constitutive features and determines their influence on the qualification and appointment of punishment.